Autism Spectrum Disorder Genes: Disease-Related Networks and Compensatory Strategies - Lim, Hye Kyung; Yoon, Jong Hyuk; Song, Minseok (Frontiers in Molecular Neuroscience, 2022)
The mammalian brain comprises structurally and functionally distinct regions. Each of these regions has characteristic molecular mechanisms that mediate higher-order tasks, such as memory, learning, emotion, impulse, and motor control. Many genes are involved in neuronal signaling and contribute to normal brain development. Dysfunction of essential components of neural signals leads to various types of brain disorders. Autism spectrum disorder is a neurodevelopmental disorder characterized by social deficits, communication challenges, and compulsive repetitive behaviors. Long-term genetic studies have uncovered key genes associated with autism spectrum disorder, such as SH3 and multiple ankyrin repeat domains 3, methyl-CpG binding protein 2, neurexin 1, and chromodomain helicase DNA binding protein 8. In addition, disease-associated networks have been identified using animal models, and the understanding of the impact of these genes on disease susceptibility and compensation is deepening. In this review, we examine rescue strategies using key models of autism spectrum disorder.